Impacts of BIPA Teaching Policy on Capacity Building of Course and Training System - Aryawan, Fatah Nasikh; Pamungkas, Alim Harun; Sonhadji, Ahmad (Journal of Nonformal Education, 2017)
The policy of Indonesian Language for Foreign Speakers (BIPA) teaching in the frame of state language internationalisation is a new form of educational policy in Indonesia. BIPA teaching is an educational policy which has been integrated with policy on culture in the context of Ministry of Education and Culture’s organisational entity and its policy ecosystem. This article is written based on a research in accordance with theories in policy analysis. Research findings are: (1) explanation about the content of BIPA teaching policy and its supporting policies, (2) policy implementation which consists of: (a) upgrading the status of national language center, and (b) the program of BIPA teaching in foreign countries, and (3) positive impacts of the policy implementation, which are: (a) establishment of BIPA teachers’ new association (APPBIPA), and (b) ongoing efforts to enhance the management capacity of BIPA non formal education and training organisations (LKPs), such as making the BIPA trainees’ competency standard (SKL), forming the BIPA competency certification body (LSK) and the BIPA profession certification body (LSP).